Acetophenone-benzaldehyde ethylenediamine modified electrodes for the determination of metal ions in aqueous solutions - Syaza Azhari, 1990-, author; Rahmalan Ahamad, supervisor; Farediah Ahmad, supervisor; Fakulti Sains (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Ph.D (Kimia)) - Universiti Teknologi Malaysia, 2017